Pembentukan Subjektivitas Buruh di Dalam Pabrik: Etnografi Buruh Perempuan di Jember (The Labour Subjectivity Formation in Within A Factory: Etnography Women Labour in Jember) - Yanto, Nuril Fahbi; Bharata, Lukman Wijaya (University of Jember, 2019)
AbstractIn a n i ndu s t r i a l f a c t o r y, l a b o r ers ha ve a n im po r t an t r o le in c a rr yi n g ou t t h e p r odu cti o n p r o c e ss W h erew o r k e r s w h o w o r k m u s t a l w a ys b e d i s ci p li n ed an d qu ick s o t ha t t h e p r odu cti o n p r o c e s s r un s p erfe c tly. O n eo f t h e f a ct o r ies in J e m b e r t ha t is e xp e r ie n ci n g d e v el o p me n t in ag r o i ndu s t r y is PT. Mi tr a t an i D u a T u j uhT h is f a ct o r y s ells ag r i c u lt u r a l p r odu cts. P r odu cts f r o m t h is f a ct o r y ha ve b e e n e xpo r ted to f o r ei g nc oun t r ies. To m a ke t h e b e s t p r odu ct, t h e f a ct o r y r e qu i r es e xp ert is e f r o m w o men w o r k ers s o t ha t t h ep r odu cti o n p r o c e s s c on ti nu es. I n f a ct o r ies, fem a l e w o r k e r s o c cup y a n im po r t an t r o le in t h e p r odu cti o np r o c e s s s u ch a s s o r ti ng c o i n a n d p a c k i ng I n o r d er f o r t h is p r odu cti o n p r o c e s s to r u n in a c co rd an ce w itht h e w i s h es o f t h e f a ct o r y, t h e f a ct o r y f o r med w o men w o r k e r s a c co r d i n g to t h eir n e ed s S o t ha t f a ct o r ies c a ndo mi na te fem a le w o r k e r s an d c au s e w o men wo r k e r s to no t b e ab le to un ite to f o r m a un i o n f o r t h em. T h ispap er is a r e s e a r ch c a rr ied ou t f o r f a ct o r y w o r k e r s o f PT. Mi t r a t an i D u a T u j u h u s i n g qua litative met hod san d e t h n og r aph ic a p p r oa c h es. T h e t h e o r y u s ed in t h is s t ud y is c o mm od ity feti s m, i d e o l og ic a l a p pa r a t u s ,an d f a ct o r y p r odu cti o n s ystem s T h e r es u l t s o f t h is s t ud y i n cl ud e t h e p r odu cti o n p r o c e ss t h e f o r m a ti o n o fl a b o r s ub jects in t h e p r ese n ce o f f a ct o r ies, t h e f o r m a ti o n o f l a bo r s ub jects in t em p er a t u r e c ond itio n s inf a ct o r ies, t h e f o r m a ti o n o f fem a l e l abo r ers in f a ct o r ies, an d t h e f o r m a ti o n o f fem a le l abo r ers in t h e f a mily.On t h e o t h er h a nd f a c t o r ies do mi na te fem a le w o r k e r s u s i n g s e v er a l met hod s Fi rs t, i n terp o l a ti n g f em a lew o r k e r s t h r oug h f a ct o r y r u les. S e cond f a ct o r y hu m a n i s m to fem a le w o r k e r s T h i r d t h e f a ct o r y p r o vi d esn e go ti a ti o n s f o r w o men w o r k e rsKe y w o r d s fem a le laborer f a ct o r f o r m a ti o n o f l a b o r i n terpell a ti o n